Academic Writing Challenges of EFL Learners and Teachers’ Proficiency in Pakistani Higher Education - Khalid Mahmood (Journal of Research in Social Sciences, 2021)
This mixed methods research study is aimed at exploring the challenges of academic writing faced by EFL leaners and teachers’ proficiency at higher education of Pakistan. Explanatory sequential design has been used for collection of data. Survey technique was employed to collect quantitative data from 19 EFL leaners enrolled for MA TEFL in a public sector university of Pakistan. Qualitative data was collected through content focused synthesis of online documents available at official websites of Higher Education Commission (HEC) of Pakistan and a newspaper. The study found salient academic writing challenges of EFL learners: (1) references and citations (2) cohesion and coherence (3) choosing a worthwhile topic (4) language usage and (5) others. However, the proficiency level of teachers found as: (1) loopholes in selection criteria of teachers (2) lack of pedagogical and analytical skills and (3) incompatibility of curriculum. The study recommends revision of teachers’ selection criteria and syllabus of English language.